Assessing the ICT competencies of out-of-school youth in a village in Naga city: A basis for developing a training program - Trinidad, Glenn A. (Edelweiss Applied Science and Technology, 2025)
This study aimed to assess the Information and Communication Technology (ICT) competencies of out-of-school youth (OSY) in Naga City, Cebu, as a basis for developing a targeted training program. Using a descriptive-evaluative research design, 50 OSY participants aged 16–24 were evaluated through structured questionnaires and practical exercises that covered hardware assembly, operating system installation, networking, office productivity software, Google Suite, and the utilization of online tools. Findings revealed significant deficiencies in networking (mean = 1.85), operating system installation (mean = 2.10), and online tools utilization (mean = 1.93), while moderate proficiency was observed in office productivity software (mean = 2.35) and Google Suite (mean = 2.58). These results informed the design of a hands-on training program tailored to address specific skill gaps. Post-training assessments showed marked improvements in digital collaboration and productivity tools, though advanced technical skills still required further development. The study concludes that targeted ICT training has a significant impact on enhancing digital literacy and employability among marginalized youth. Practical implications include the need for sustained, skill-specific interventions to bridge the digital divide and prepare OSY for meaningful participation in the digital economy.